Zebrafish as a model system for studying reproductive diseases - Zha, Wenwen; Hu, Weitao; Ge, Chenkai; Chen, Jianjun; Cao, Zigang (Frontiers in Cell and Developmental Biology, 2024)
Reproductive system diseases have become a major health challenge facing humans, so extensive investigations are needed to understand their complex pathogenesis and summarize effective treatments. In the study of reproductive diseases, mice are the most commonly used animal model. However, the cost and time required to establish mouse animal models are high. The existing zebrafish model can solve this problem well. Zebrafish is an animal model with great application prospects and has lots of advantages, including high degree of genetic conservation with humans, short reproductive cycle, transparent embryos, and rapid growth, providing unique opportunities for high-throughput drug screening and identification of potential treatments. Researchers have successfully used chemical induction, physical damage, gene editing technology, etc., to induce reproductive system damage in zebrafish to study the biological processes related to its reproductive diseases. Therefore, in this review, the main models and related advantages of zebrafish in reproductive diseases are summarized, the pathological mechanisms of zebrafish as a reproductive disease model are clarified, and new perspectives and valuable insights are provided for the treatment of human reproductive diseases. The literature and data cited in the review are all from PubMed, covering important research results on zebrafish reproductive diseases in the past 10 years.